Field Correlations of Multimode Optical Beams in Underwater Turbulence - Baykal, Yahya; Gokce, Muhsin C.; Ata, Yalcin; Gercekcioglu, Hamza (Optica Publishing Group, 2024)
For multimode optical beams, field correlations at the receiver plane are found in underwater turbulence. Field correlations of single high order beams in underwater turbulence are special cases of our formulation. Variations of field correlations against the underwater turbulence parameters and the diagonal length from various receiver points are examined for different multimode and single high order beams. Stronger underwater turbulence is found to reduce the field correlations of multimode and single high order optical beams. The results will be of help in heterodyne detection analysis and fiber coupling efficiency in an underwater medium experiencing turbulence. (c) 2024 Optica Publishing Group
Gokce, Muhsin Caner/0000-0003-4465-1983; Baykal, Yahya/0000-0002-4897-0474; Gercekcioglu, Hamza/0000-0002-3587-9196